2004
DOI: 10.1136/bmj.38128.631319.ae
|View full text |Cite
|
Sign up to set email alerts
|

Predicting bacterial cause in infectious conjunctivitis: cohort study on informativeness of combinations of signs and symptoms

Abstract: Objective To find an efficient set of diagnostic indicators that are optimally informative in the diagnosis of a bacterial origin of acute infectious conjunctivitis. Design Cohort study involving consecutive patients. Results of index tests and reference standard were collected independently from each other. Setting 25 Dutch health centres. Participants 184 adults presenting with a red eye and either (muco)purulent discharge or glued eyelid(s), not wearing contact lenses. Main outcome measures Probability of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(81 citation statements)
references
References 10 publications
4
75
1
1
Order By: Relevance
“…Brook,4 in a study of acute conjunctivitis in children, found that control eyes were culture-positive 90.9% of the time. Perkins et al, 5 in a similar study, recovered bacterial isolates in 90.6% of control eyes. Moreover, all three of the abovementioned bacteria were found to be colonizing control eyes.…”
mentioning
confidence: 86%
“…Brook,4 in a study of acute conjunctivitis in children, found that control eyes were culture-positive 90.9% of the time. Perkins et al, 5 in a similar study, recovered bacterial isolates in 90.6% of control eyes. Moreover, all three of the abovementioned bacteria were found to be colonizing control eyes.…”
mentioning
confidence: 86%
“…Rietveld study stated that glued eye, itch and history of conjunctivitis provided optimal discrimination between patients with bacterial and viral aetiology, a history of both infectious conjunctivitis and itch make the probability of bacterial aetiology less likely, while glued eye is strong hint for bacterial aetiology [18]. On the other hand a very valuable report coming after searching the literature by Gigliotti, stated that he was unable to find evidence of the diagnostic usefulness of clinical signs, symptoms or both in distinguishing bacterial conjunctivitis from viral conjunctivitis and he recommended further researches to provide general practitioners with easy to use diagnostic tools to differentiate bacterial from viral conjunctivitis to tailor antibiotic prescriptions [21].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a study by Rietveld et al in adults found a similar connection between these findings and bacterial etiologies. 5 We appreciate the value of using a slit lamp when examining the eyes. However, we do not believe that its use is vital in making the diagnosis of conjunctivitis.…”
Section: In Replymentioning
confidence: 99%